Issues on effective energy management system for vertical development of urban mosque in Malaysia - Utaberta, Nangkula; Mohd Sauffie, Nur Fatin; Supni, Siti Asikin; Asif, Nayeem (Centre for Innovative Architecture and Built Environment (SErAMBI), Faculty Engineering and Built Environment, Universiti Kebangsaan Malaysia, 2018)
Contemporary urban mosques in Malaysia shows the tendency for vertical progression in their physical layout. The general climate of Malaysia and also the operation schedule of the mosque have impact on the demand for the energy uses by the mosque. The energy management not only involves the electricity problem but also the water resources for five time daily used. The objectives of this study include determination of energy efficiency, water efficiency, the indoor air quality and also the sustainable site planning management for mosque that will lead to effective way of saving energy used by the mosque. This study presents the analysis of collected data from literature survey as well as evaluating two case studies in Malaysia. The aim is to assess and look forward to the energy used by the urban mosque having vertical progression with the new high-end technology and the well-managed design mosque as a step towards a comprehensive study their effective way of management of energy system.